Perbedaan peningkatan jumlah mikronukleus antara mukosa gingiva dan mukosa bukal akibat paparan radiografi panoramik digital - Shintia Olvya; Isti Rahayu Suryani; Rurie Ratna Shantiningsih (Ikatan Radiologi Kedokteran Gigi Indonesia, 2019)
Objectives: The purpose of this study was to determine the differences in the number of micronuclei between the gingival mucosa and the buccal mucosa due to exposure to digital panoramic radiography. Material and Methods: This study used 10 healthy individuals aged 18-25 years. Exfoliated epithelial cell samples from the gingival and buccal mucosa were taken from the patient on the 10th day after exposure to digital panoramic radiography. The coloring method used is Feulgen-Rossenbeck. Results: The micronucleus calculation was performed by the method of assessing 1000 cells per slide using a binuclear light microscope with a magnification of 400x. The results of the analysis by unpaired T test showed that the difference in the increase in the number of micronuclei was statistically significant (p <0.05). The average difference in the increase in the number of micronuclei was 3.5 ± 0.767. There is a significant difference in the increase in the number of micronuclei between the gingival mucosa and the buccal mucosa due to exposure to digital panoramic radiography with an increase in the number of micronucleus in the buccal mucosa higher than the gingival mucosa. Conclusion: The conclusion of this study is that digital panoramic radiography can cause genotoxic effects on the gingival and buccal mucosa. Digital panoramic radiography is used if needed.